Assessing yield and plant traits of Loco chile from the Sierra Nevada of Puebla - Salinas-Romero, Mayra; López, Pedro Antonio; Gil-Muñoz, Abel; Toledo-Aguilar, Rocío; López-Sánchez, Higinio (Ecosistemas y Recursos Agropecuarios, 2025)
Currently, the yield and vegetative traits of national long chiles such as Guajillo, Pasilla, etc. have been defined, but we do not have the same knowledge about regional chiles, such as Loco. The objective was to determine the yield of the Loco chile and to specify the main plant traits that influence it. The experimental unit consisted of two 5 m long rows, with a distance of 80 cm between them and 30 cm between plants. Six varieties of Loco chile were compared with the Guajillo, Pasilla, Puya, de Árbol and Serrano chile, registering 17 plant and yield traits. The Loco chili obtained an average fresh yield (13.2 t ha-1) statistically similar to the controls except for the de Árbol chile (8.3 t ha-1). According to the correlation analysis, the variables that influenced yield were: days to flowering (in an interval of 46 to 55 days), plant height (62-71 cm), stem diameter (10-12 mm), seeds per fruit (197-240) and number of fruits per plant (20 to 28). In conclusion, the Loco chile cultivar has similar yields to the long chile peppers of national importance, since, in general, its plant traits are also similar. The Loco 404 variety is a tall, compact, early-flowering plant with a yield of 15.5 t ha-1 and a characteristic striped exocarp.